Hepatitis C virus translation preferentially depends on active RNA replication. - Helene Minyi Liu; Hideki Aizaki; Keigo Machida; J-H James Ou; Michael M C Lai (PLoS ONE)
Hepatitis C virus (HCV) RNA initiates its replication on a detergent-resistant membrane structure derived from the endoplasmic reticulum (ER) in the HCV replicon cells. By performing a pulse-chase study of BrU-labeled HCV RNA, we found that the newly-synthesized HCV RNA traveled along the anterograde-membrane traffic and moved away from the ER. Presumably, the RNA moved to the site of translation or virion assembly in the later steps of viral life cycle. In this study, we further addressed how HCV RNA translation was regulated by HCV RNA trafficking. When the movement of HCV RNA from the site of RNA synthesis to the Golgi complex was blocked by nocodazole, an inhibitor of ER-Golgi transport, HCV protein translation was surprisingly enhanced, suggesting that the translation of viral proteins occurred near the site of RNA synthesis. We also found that the translation of HCV proteins was dependent on active RNA synthesis: inhibition of viral RNA synthesis by an NS5B inhibitor resulted in decreased HCV viral protein synthesis even when the total amount of intracellular HCV RNA remained unchanged. Furthermore, the translation activity of the replication-defective HCV replicons or viral RNA with an NS5B mutation was greatly reduced as compared to that of the corresponding wildtype RNA. By performing live cell labeling of newly synthesized HCV RNA and proteins, we further showed that the newly synthesized HCV proteins colocalized with the newly synthesized viral RNA, suggesting that HCV RNA replication and protein translation take place at or near the same site. Our findings together indicate that the translation of HCV RNA is coupled to RNA replication and that the both processes may occur at the same subcellular membrane compartments, which we term the replicasome.